English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please solve and explain this equation:
5/2t-t=3+3/2t

What does t equal?

Thanks for your help

2007-01-10 13:20:24 · 9 answers · asked by Anonymous in Science & Mathematics Mathematics

9 answers

Multiply both sides by 2t:

5 -2t^2 = 3t + 3

-2t^2 - 3t +2 = 0

2t^2 + 3t - 2 = 0

(2t - 1)(t + 2) = 0

t = 1/2 t = -2

Bozo

2007-01-10 13:27:40 · answer #1 · answered by bozo 4 · 0 1

5/2t-t=3+3/2t
3/2=3+3/2t (subtract t from 5/2t)
0=3

0 is not equal to 3, so there is no solution.

2007-01-10 21:26:15 · answer #2 · answered by      7 · 0 0

I assume that you mean 5/(2t)-t=3+3/(2t) ?in this way :
multipy the equation by 2t so you have :
5-2t^t=3t+3
So 2t^2+3t-2=0
and then t=0.5 and -2
but if you mean (5/2)t-t=3+(3/2)t it is much easier :
=>(5/2-1)t=3+3/2t
=>(5/2-1-3/2)t=3
=>0t=3 in this way the equation dosn't have any answer!

2007-01-10 21:33:49 · answer #3 · answered by Arash J 2 · 0 1

5/2t-t=3+3/2t

multiply each side by 2 to remove the fractions gives:
5t-2t=6+3t

Simplify gives:
3t = 6 + 3t

Subtract 3t from each side:
0 = 6

Since zero does not equal 6 there is no solution.

2007-01-10 21:29:04 · answer #4 · answered by Edgard L 2 · 0 1

multiply both sides by 2t and you'll get:

5-2t^2 = 6t+3

make it all equal to zero so

-2t^2 - 6t +2 = 0

do the quadratic equation and your answers should be around

-3.3028 and .3028

2007-01-10 21:33:32 · answer #5 · answered by Tom 1 · 0 0

first you multiply both sides by '2t' to eliminate them. the equation should look like:
5-t=3+3 or 5-t=6
subtract 5 from both sides to have
-t=1
divide each side by negative one and you will get the answer of
t= -1 (negative one)

2007-01-10 21:29:21 · answer #6 · answered by Anonymous · 0 0

i believe it is undefined. when i tried to work it out by subtracting 3/2t from both sides to get t on one side only, i got t-t which is 0 and the other side was 3... 0=3? no, thats undefined.

2007-01-10 21:27:43 · answer #7 · answered by ashesanne 2 · 0 0

5/2t - t = 3 + 3/2t

5/2t - 3/2t -t = 3

(2/2t -t = 3 )*2t

2 - 2t^2 = 6t ----->> 2t^2 +6t -2 =0 and factorise.

2007-01-10 21:31:16 · answer #8 · answered by Diora 3 · 0 0

5/2t-t = 3/2t
bring the other one over...
3/2t-3/2t=3
0=3
and sumthing mustave gone wrong or im just plain dumb

2007-01-10 21:30:00 · answer #9 · answered by Turtle~ 3 · 0 0

fedest.com, questions and answers